Kajian Peningkatan Keselamatan Penumpang Bus AKDP/AKAP Melalui Pembinaan Pengemudi dan Fasilitas Keselamatan di Bali - Setyabudi, Besar (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2011)
Infrastructures' quality on bus safety are depends on some elements supporting such as the bus company, driver, spare parts, bus compete, and the bus itself Based on the driver's behavior some points that should be concerns are the driver's safety awareness and illegal driver license, which affecting the driver's behavior such as; driving carelessly, disobey the passengers' safety and disobey the traffic signs. The goal of this study is to find out the quality of AKDP/AKAP bus safeh/s infrastructures and passengers safety's factors. Some recommendations are expected to be delivered as the results of the study as the improvement of the quality of AKDP/ AKAP bus safety's infrastructures in order to support the passengers' safety in Bali. This is a descriptive study, with the assumptions that the cause of accidents is dominated by human error which is the driver. The result of the study showed that there are some factors play important roles as the cause of accident and the main factor in bus accident dealing with the infrastructure's safety improvement is vehicles' calibration.Keywords: safety facilities, bus